Metalinguistic Knowledge of Salient vs. Unsalient Features: Evidence From the Arabic Construct State. (17th February 2017) - Azaz, Mahmoud
Abstract: This study examined to what extent English‐speaking learners of Arabic demonstrated varied metalinguistic knowledge of a salient feature (head‐direction) vs. an unsalient feature (definiteness) in the Arabic construct state. In addition, it examined whether this knowledge was utilized in form‐focused task performance. In the target construction, the head is canonically positioned before the complement (left‐headed) and the definite marker is prefixed to the complement. Salience of these two features was operationalized in terms of inherent prominence; head‐direction was determined to be more salient than the monosyllabic proclitic definite article. Metalinguistic knowledge was conceptualized in terms of the learners' ability to selectively focus attention, provide explicit explanations, and use metalanguage. A beginner group (N = 20) and an intermediate‐proficiency group (N =18) completed a multiple‐choice task. A retrospective think‐aloud interview with 10 participants from each group sought to capture the manifestations of their metalinguistic knowledge. The quantitative‐qualitative analysis revealed that while both groups demonstrated complex metalinguistic knowledge of head‐direction, they did not demonstrate the same knowledge of definiteness placement. A follow‐up correlation showed strong connections between manifestations of metalinguistic knowledge and response type distribution in the task. The role of metalinguistic knowledge in language learning and relevant pedagogical focus‐on‐form implications are discussed.